Women workers and globalization : emergent contradictions in India - Mazumdar, Indrani (Stree, 2007)
Investigating the impact of globalisation on women workers, the author demystifies the phenomenon of globalisation, offering an overview of its prime drivers, processes and forces. Four sectoral studies of women workers are provided: two on factory women in garment exports and electronics; the third on home-based workers in a range of manufacturing processes and industries and the fourth on middle class women working in Information Technology Enabled Services (ITES). Offering an analysis of the effects of the changed policy paradigms on women workers, of global sectoral trends and their ramifications, and cutting through the hype on India's growth statistics, the author makes a valuable contribution to the reality of women's work in conditions of increasing insecurity. Study conducted among four sectors of women workers in and around Delhi capital region.